2016
DOI: 10.3389/feart.2016.00027
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Recent Advances in Red-Clay Environmental Magnetism and Paleoclimate History on the Chinese Loess Plateau

Abstract: The red-clay sequence on the Chinese Loess Plateau (CLP) was deposited during the late Miocene-Pliocene and is encoded with important information of past climate changes. However, it has received much less study in comparison to the overlying Pleistocene loess-paleosol sequence. In this paper, we review recent progress in characterizing the environmental magnetic parameter-based paleoclimate history recorded by the red-clay sequence. Several key conclusions are as follows. (1) the red-clay and the loess-paleos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 81 publications
0
24
0
Order By: Relevance
“…In contrast, in palaeosol layers, the dominant magnetic minerals are pedogenic maghemite and magnetite, with minor amounts of magnetite, and in red clay layers, the dominant magnetic mineral is pedogenic haematite with minor pedogenic maghemite (Xie, 2008). As mentioned above, the climate when the red clay layers formed was warmer and more humid, and pedogenesis was stronger; consequently, a large amount of ultrafine strongly magnetic minerals such as maghemite and magnetite formed (Nie et al, 2007(Nie et al, , 2014(Nie et al, , 2016. Previous studies have shown that the low-temperature oxidation (LTO) of magnetite is a common process during weathering (Van Velzen and Dekkers, 1999) that gradually alters magnetite into maghemite (magnemitisation).…”
Section: Comparison Between χ and δ 18 O And The Corresponding Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, in palaeosol layers, the dominant magnetic minerals are pedogenic maghemite and magnetite, with minor amounts of magnetite, and in red clay layers, the dominant magnetic mineral is pedogenic haematite with minor pedogenic maghemite (Xie, 2008). As mentioned above, the climate when the red clay layers formed was warmer and more humid, and pedogenesis was stronger; consequently, a large amount of ultrafine strongly magnetic minerals such as maghemite and magnetite formed (Nie et al, 2007(Nie et al, , 2014(Nie et al, , 2016. Previous studies have shown that the low-temperature oxidation (LTO) of magnetite is a common process during weathering (Van Velzen and Dekkers, 1999) that gradually alters magnetite into maghemite (magnemitisation).…”
Section: Comparison Between χ and δ 18 O And The Corresponding Mechanismmentioning
confidence: 99%
“…Environmental magnetism as a proxy has been widely used in studies of palaeoclimatic changes in Quaternary loess-palaeosol successions (Evans and Heller, 2001;Hao and Guo, 2005;Maher and Possolo, 2013;Maher, 2016), Tertiary red clay successions (Liu et al, 2003;Nie et al, 2008;Zhao et al, 2016), and other older aeolian deposits (Hao et al, 2008;Zhan et al, 2011), as well as in studies of lake sediments (Snowball et al, 1999;Fu et al, 2015;Hu et al, 2015) and marine sediments (Larrasoaña et al, 2008;Peters et al, 2010). In this paper, we review previous work (mainly in terms of geochronology and palaeoclimatology) and report some defects in the established chronological framework and palaeoclimatic record.…”
Section: Introductionmentioning
confidence: 97%
“…Magnetic minerals could be converted to goethite or other weakly magnetic minerals owing to the high water content of wet grassland, but converted to ferrimagnetic minerals in dry grassland, a hypothesis raised by Nie et al (2016) based on the magnetic properties of redclay on the Chines Loess Plateau. However, the different mineral transform route needs detailed study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These eolian deposits can be divided into two parts: the well-known Quaternary loess-paleosol sequence and the underlying Miocene-Pliocene Red Clay sequence. While the climatic history recorded by Quaternary loess-paleosol sequences is relatively well constrained, the climatic significance of Red Clay sequences is far from established (An, 2014;Ao et al, 2016;Nie et al, 2016). Existing Miocene-Pliocene paleoclimate records from the semi-arid CLP (An et al, 2001(An et al, , 2005Nie et al, 2014;Ao et al, 2016), arid western China (Miao et al, 2012), and humid South China (Clift et al, 2014) provide contrasting information on climate variability over this time interval.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, magnetic parameters are widely used to investigate pedogenic weathering, monsoon evolution, aridification history, and global climate change recorded in Quaternary loess-paleosol sequences (Kukla et al, 1988;An et al, 1991;Verosub et al, 1993;Florindo et al, 1999;Evans and Heller, 2001;Deng et al, 2005Deng et al, , 2006Liu et al, 2007Liu et al, , 2012Liu et al, , 2013Liu et al, , 2015. However, considerably less environmental magnetic research has focused on the underlying Miocene-Pliocene Red Clay sequences (Nie et al, 2016). Here, we investigate late Miocene-early Pliocene climate change in East Asia; new mineral magnetic records of a Red Clay succession from Shilou (36°55' N, 110°56' E) on the eastern CLP form the basis for our paleoclimatic interpretations.…”
Section: Introductionmentioning
confidence: 99%